Responses of soil microbial community and enzymes during plant-assisted biodegradation of di-(2-ethylhexyl) phthalate and pyrene. Issue 7 (7th June 2019) - Wu, Kejun; Dumat, Camille; Li, Hanqing; Xia, Hanping; Li, Zhian; Wu, Jingtao
Abstract: A pot experiment was conducted to explore the plant-assisted degradation efficiency of di-(2-ethylhexyl) phthalate (DEHP) and pyrene. Three plant species: Ceylon spinach, sunflower, and leaf mustard were cultivated in co-contaminated soils under three contamination levels: control (T0), 20 mg kg −1 (T20), and 50 mg kg −1 (T50). The results showed that a higher DEHP and pyrene degradation efficiency was observed evidently in planted cases, increasing from 42 to 53–59% (T0), 61 to 65–76% (T20) and 52 to 68–78% (T50) for DEHP, and from 22 to 30–49% (T0), 58 to 62–72% (T20), and 54 to 57–70% (T50) for pyrene. Under T20 contamination level, soil phospholipid fatty-acid analysis depicted the increased microbial biomass in rhizosphere, especially the arbuscular mycorrhizal fungus that is effective for the degradation of organic pollutants. The study also revealed that the activities of dehydrogenase, acid phosphomonoesterase, urease, and phenol oxidase negatively correlated with pollutant concentration. In general, the removal rate of DEHP and pyrene was highest in the soil planted with leaf mustard for each contamination level considered. For soils at T20 level, sunflower and leaf mustard appeared as interesting phytoremediation plants due to the improved removal rates of organic pollutants and the soil microbial activity.